The Acceptance of Technology: Use of the Mobile App in the Extension of Rural Loans During the Pandemic - Briza, Jorge Andre [UNESP]; Alves Garcia, Sheila Farias [UNESP]; Lago Attadia Galli, Lesley Carina do [UNESP] (Russian Soc Historians & Archivists, 2023)
The study identified the usefulness, ease of use, risk, and trust impacts on the intention to use the mobile app in extending rural loans. An investigation was carried out through a survey with a quantitative approach, measuring the relationship between the constructs through scales already validated in previous studies. The approach to the target audience made it possible to map all rural producer customers eligible for the extension of rural loans in 398 bank branches in the State of Sao Paulo, sending a questionnaire to 900 customers in 20 different municipalities and obtaining responses from 79 customers. The result found that the intention to use is influenced by usefulness and this is impacted by the easiness, while trust reduces the perception of risk. However, it does not prove that ease of use and risk directly affect intention, nor the relevance of risk in usefulness. The survey with rural producers during the launch of the digital loan extension service and the restrictions on movement and social isolation imposed by the COVID-19 pandemic allowed for the aggregate investigation of a circumstantial situation however with permanent impacts. The focus on the rural producers' niche allows the improvement of existing knowledge about the utility factor and enables different perspectives for future research that aims to measure the relationship between risk perception and ease of use as antecedents of intention to use. It will allow financial institutions to leverage strategies to manage the relationship with this niche.
Keywords: technological acceptance model; mobile banking; rural extensions